2018
DOI: 10.1039/c7cp07953b
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and magnetic properties of monolayer α-RuCl3: a first-principles and Monte Carlo study

Abstract: Recent experiments revealed that monolayer α-RuCl 3 can be obtain by chemical exfoliation method and exfoliation or restacking of nanosheets can manipulate the magnetic properties of the materials. In this present paper, the electronic and magnetic properties of α-RuCl 3 monolayer are investigated by combining first-principles calculations and Monte Carlo simulations. From first-principles calculations, we found that the spin configuration FM corresponds to the ground state for α-RuCl 3 , however, the other ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 74 publications
3
49
0
Order By: Relevance
“…A somewhat orthogonal approach is to neglect quantum effects completely and perform Monte Carlo (MC) simulations of the classical Heisenberg model. [11][12][13][14] In contrast to renormalized spin-wave theory, the MC approach includes all correlations in the model, but does not take into account the quantum nature of spins. It has recently been shown that the renormalized spin-wave theory yields qualitatively wrong results in systems with large magnetic anisotropy and MC simulations appear to be the most appropriate choice for extracting critical temperatures from Heisenberg models in 2D.…”
Section: Introductionmentioning
confidence: 99%
“…A somewhat orthogonal approach is to neglect quantum effects completely and perform Monte Carlo (MC) simulations of the classical Heisenberg model. [11][12][13][14] In contrast to renormalized spin-wave theory, the MC approach includes all correlations in the model, but does not take into account the quantum nature of spins. It has recently been shown that the renormalized spin-wave theory yields qualitatively wrong results in systems with large magnetic anisotropy and MC simulations appear to be the most appropriate choice for extracting critical temperatures from Heisenberg models in 2D.…”
Section: Introductionmentioning
confidence: 99%
“…where J1,J2 and J3 are the exchange interactions parameter . The exchange parameter J can be obtained by calculating the relative energy differences between ferromagnetic (FM), ferrimagnetic (FiM) and antiferromagnetic states (AFM).…”
Section: Resultsmentioning
confidence: 99%
“…where J 1 ; J 2 and J 3 are the exchange interactions parameter. [43] The exchange parameter J can be obtained by calculating the relative energy differences between ferromagnetic (FM), ferrimagnetic (FiM) and antiferromagnetic states (AFM). The same Hamiltonian can be used for both molecular approach (MA) as well as for the periodic approach (PA).…”
Section: Exchange Model and Ferromagnetismmentioning
confidence: 99%
“…Transition metal trihalides provide a rich family of ma-terials with a wide range of electronic, optical and mechanical properties in which also low dimensional magnetism can be examined, and therefore rapidly increasing theoretical researches exists on this area. [20][21][22][23][24] In our previous study, we systematically investigate the electronic and magnetic properties of an α-RuCl 3 monolayer using DFT and MC simulations, 25 and our cleavage energy calculations give smaller value than that of graphite, which means that the α-RuCl 3 monolayer can be easily obtained from its bulk phase and also we find that it is stable 2D intrinsic ferromagnetic semiconductor. Similarly, a class of 2D ferromagnetic monolayers CrX 3 (X= Cl, Br, I) is studied by Liu et al 26 by using first principle calculations combined with MC simulations based on the Ising Model.…”
Section: Introductionmentioning
confidence: 87%